A new Diplura species from Georgia caves, Plusiocampa (Plusiocampa) imereti (Diplura, Campodeidae), with morphological and molecular data - Sendra, Alberto; Palero, Ferran; Sánchez-García, Alba; Jiménez-Valverde, Alberto; Selfa, Jesús; Maghradze, Eter; Barjadze, Shalva (European Journal of Taxonomy, 2021)
A new dipluran species, Plusiocampa (Plusiocampa) imereti Sendra & Barjadze sp. nov., from the deep zone in three caves in the Imereti region, Georgia, is described. This new troglobitic Plusiocampa is an addition to four others known Diplura from around the Black Sea region, two Dydimocampa and two Plusiocampa s. str. The present study also provides the first CO1 sequences for the Plusiocampinae taxa and the first molecular data for cave-dwelling Plusiocampa species. Although bootstrap values were low, the maximum-likelihood phylogenetic tree grouped Plusiocampa (P.) imereti Sendra & Barjadze sp. nov. with two Plusiocampa s. str. species from Eastern Europe. Morphologically, P. (P.) imereti Sendra & Barjadze sp. nov. is closely related to two cave-dwelling species: Plusiocampa (Plusiocampa) glabra Condé, 1984 and Plusiocampa (P.) chiosensis Sendra & Gasparo, 2020. The new species can be distinguished by the presence of lateral anterior macrosetae on metanotum, more uneven claws, and the presence of 2+2 lateral anterior macrosetae on middle urotergites. The five species currently known for the Black Sea region inhabit caves located at low altitude but with no influence from former glacial or permafrost processes.